以院校合作模式推動課程發展 Curriculum Development through an Institution-School Partnership Approach - 林碧霞Bick-Har Lam (Higher Education Foundation, 2010)
本文提出香港現今師資培訓及中學校教育的局限性，並以行動研究的角度去尋找、探討及描述一個創新的教學法：「以院校合作模式推動課程統整」。文中描述這個院校合作計畫的理論架構、實踐模式及研究結果。院校合作提供啟導以及院校協作推動課程發展的機會，讓準老師把他們已涉獵的理論和教學法實踐在真實的教學情景中，師資培訓不再是紙上談兵。這個實景性學習能激發準老師的學習動機的同時，也能推動學校的課程發展。此外，院校合作的設計與實踐也融合了課程統整的原素：把學科分割的知識在有意義的教學主題下重新統合。因此，作為門徑去推動中學課程統整的院校合作計劃亦能讓中學生明白知識與生活是息息相關，讓他們體會學會學習的真諦。 Addressing the limitations of the current teaching training methods, this study adopts action research as a tool to examine the effectiveness of a new model of teaching known as the institute-school partnership in a teacher education programe in Hong Kong. The paper discusses the framework, design and implementation of this new partnership mode for a group of nine pre-service teachers, and how it can serve as a professional strategy to promote integrated curriculum development in schools. The Institution-school partnership project provided mentoring support that encouraged student-teachers to take part in curriculum development in school, student-teachers was able to apply pedagogical knowledge into real life context, and learned from experience alongside learning from text. This method enhanced the learning motivation of student-teachers at this pre-service period for better equipping themselves for the school workplace, at the same time highly promoted curriculum development of the participating school by adopting the concept of integration to achieve effective learning, within the current segregated curriculum structure in school. The study uses integrated curriculum as a cutting point to link up partnership with the teacher education institute and school teachers, the lessons learnt can be shared to promote curriculum development in schools which better serves the needs of learning for students in schools.